Crosstalk between lipid metabolism and macrophages in atherosclerosis: therapeutic potential of natural products - Qian, Taoming; Guo, Donghao; Sun, Lu; Chi, Ming; Ma, Xiaoshuang; Jin, Juan (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis is a highly prevalent cardiovascular condition that affects individuals worldwide. Despite ongoing research into its treatment and prevention, atherosclerotic cardiovascular disease continues to exhibit high morbidity and mortality rates. The accumulation of low-density lipoprotein cholesterol is considered a major contributor to the development of atherosclerosis, with abnormalities in lipid metabolism playing a significant role in its pathogenesis. Lipid metabolism and macrophage function are intricately interconnected, with lipid metabolism being influenced by macrophage inflammatory responses, while macrophage activity is regulated by alterations in lipid metabolism. The interaction between these two processes plays a critical role in the progression of atherosclerosis. Natural products have shown considerable promise in treating a variety of diseases, including atherosclerosis. Moreover, the modulation of lipid metabolism and macrophage crosstalk represents a key mechanism through which natural products may exert their effects. This research aims to provide new insights into the current state of research on the role of natural products in regulating this pathway and the interplay between lipid metabolism and macrophages in the context of atherosclerosis, offering potential directions for the future.